Investigation of Bauschinger effect in single and polycrystalline bulk Au with molecular dynamics simulation - Kazanc, Sefa; Canbay, Canan Aksu (Taylor & Francis Ltd, 2025)
In this study, the Bauschinger effect was investigated in single crystal and polycrystalline volumetric gold (Au) model systems, as a result of uniaxial tension-compression deformation process applied at 300 K temperature, using Molecular Dynamics (MD) simulation method. Embedded Atom Method (EAM) was used in modelling the interactions between atoms. The innovative aspect of the study is that it reveals the asymmetry in the mechanical behaviours of both single crystal and polycrystalline structures in detail and relates these behaviours to microstructural mechanisms. The asymmetry observed in the stress-strain curves between tension and compression processes showed that grain size significantly affects the intergranular motion mechanisms, grain boundaries and the relationship with yield strain in polycrystalline systems. From this relationship, Hall-Petch (HP) effect and reverse Hall-Petch effect after 3.24 nm grain size were observed. In addition, Bauschinger Effect (BE) was determined during the compressive deformations applied after the yield strain value was exceeded. In order to clarify the effect of BE on single and polycrystalline bulk Au model system, Bauschinger stress parameter (BSP) and Bauschinger Parameter (BP) were calculated and the effects were explained quantitatively.
Keywords: Polycrystalline; mechanical properties; molecular dynamics; Bauschinger effect; Hall-Petch